Immune checkpoint inhibitor-induced toxicity: a real-world analysis of the role of BMI - Spagnolo, Calogera Claudia; Ruggeri, Rosaria M.; Alibrandi, Angela; Laganà, Martina; Speranza, Desirèe; Cannavò, Salvatore; Berretta, Massimiliano; Santarpia, Mariacarmela (Frontiers in Oncology, 2025)
Immune checkpoint inhibitors (ICIs) have radically changed the therapeutic landscape of several cancers. However, only a limited number of predictive factors are currently available in clinical practice to select patients for immunotherapy. The impact of excess weight on ICI toxicity and efficacy is presently under debate. This study was aimed at evaluating the occurrence of immune-related adverse events (irAEs) among cancer patients on ICI therapy according to baseline body mass index (BMI) and gender. The association with clinical outcomes was also analyzed.Patients and methodsOne-hundred thirty patients (93 males, 37 females, median age 67 years) with diverse types of advanced cancer treated with ICIs at a single university hospital were included in the study. Patients with a previously diagnosed thyroid dysfunction were excluded from this analysis.ResultsA number of irAEs occurred in 51 patients (39.2%; 33 males, 18 females). Their development significantly correlated to BMI. Overweight/obese patients experienced a higher (59.5% vs 40.5%; p<0.001), and earlier (8 vs 10.6 weeks; p=0.003) occurrence of irAEs than normal weight patients. About 65% of overweight/obese patients had an associated dysmetabolic state (i.e., hypertension, glycemic disturbances and/or dyslipidemia) and displayed higher prevalence of irAEs than those without comorbidities (p=0.019). At multivariate regression analyses, BMI was confirmed as an independent predictor of risk for developing AEs (p<0.001), with an odds ratio (OR) of 3.182 for overweight/obese patients. No differences in BMI or gender emerged in progression-free survival (PFS) and overall survival (OS) rates.ConclusionsirAEs occurred more frequently in overweight/obese patients, mainly with metabolic abnormalities. These data underline the importance of a comprehensive clinical assessment, including weight and dysmetabolic comorbidities, of patients at baseline and during ICI therapy.